The effect of salinity on organic components of Excoecaria agallocha L. - Balasubramanian1*, P. Amuthavalli1, and P. Sivaraman2, S. Sivasankaramoorthy1, T. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present report is about the growth of the seedlings of Excoecaria agallocha in different concentration of NaCl. The observation shows that the accumulation of ions and organic components such as starch and protein increased with increasing salt concentration upto optimal level (200 mM NaCl) and decreased at higher concentration. Aminoacids and total sugar decreased with increasing concentrations of NaCl upto optimal level and increased at higher concentrations. NaCl promoted chlorophyll and carotenoid synthesis upto the optimal concentrations of 200 mM. The plant can able to tolerate upto 300 mM NaCl concentration but the optimal growth of the seedlings were observed in 200 mM NaCl concentrations.